2015
DOI: 10.1161/circgenetics.115.001165
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Proteome Analysis Reveals Increased Content of Basement Membrane Proteins in Arteries From Patients With Type 2 Diabetes Mellitus and Lower Levels Among Metformin Users

Abstract: The arterial pathology in DM does not only include increased occurrence of atherosclerotic plaques but also comprises generalized arterial alterations, that is, endothelial dysfunction, increased stiffness, extracellular matrix (ECM) changes and calcifications, which can be observed in both atherosclerotic and nonatherosclerotic parts of the arterial tree. Generalized changes in the vascular ECM have been described among patients with T1DM, that is, for glycosaminoglycans, 3 glycoproteins, 4,5 and collagens. 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
41
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 50 publications
(52 reference statements)
4
41
0
Order By: Relevance
“…This muscular artery has dimensions comparable to the coronary arteries and has proven to be a suitable model for investigations of the associations between various clinical conditions and arterial pathology; for example, in relation to fibrosis, diabetes, and medication, etc. [13,14,15,16]. The artery is usually free of atherosclerosis and intimal lesions, and the present results therefore reflect associations between the iron metabolism and generalized arterial structure and biochemistry.…”
Section: Discussionsupporting
confidence: 52%
“…This muscular artery has dimensions comparable to the coronary arteries and has proven to be a suitable model for investigations of the associations between various clinical conditions and arterial pathology; for example, in relation to fibrosis, diabetes, and medication, etc. [13,14,15,16]. The artery is usually free of atherosclerosis and intimal lesions, and the present results therefore reflect associations between the iron metabolism and generalized arterial structure and biochemistry.…”
Section: Discussionsupporting
confidence: 52%
“…The partial Spearman rank correlations were adjusted for smoking and diabetes mellitus status and intervention-size. Fisher exact test was used to test whether the distribution of significant versus nonsignificant correlated plasma-, ECM-and cytoskeletal-proteins were random, as previously described in Preil et al 22,23 Statistics were performed using Microsoft Excel, STATA 13. …”
Section: Methodsmentioning
confidence: 99%
“…The authors found an increased deposition of the basement membrane components alpha-1 and alpha-2 type IV collagen, gamma-1 and beta-2 laminin in diabetic patients [10]. …”
Section: Discussionmentioning
confidence: 99%
“…Based on previous studies with vascular tissue obtained from CABG [9, 10], the total estimated number of patients necessary for this study is 50, equally divided in DM and NDM.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation